DETERMINANTY KANAŁU KREDYTÓW BANKOWYCH W ŚWIETLE WIELOWYMIAROWEJ ANALIZY PORÓWNAWCZEJ - Jaremko, Małgorzata (Wydział Prawa i Administracji UAM, 2003)
In the article the tools of multidimensional comparative analysis are used to compare and evaluate the influence of selected determinants on the National Bank of Poland’s transmission mechanism through the bank lending channel in Poland in the years 1998-2002. The theoretical analysis describes main factors that influence the transmission mechanism and arise from banks’ and non-branks’ sectors. These are: central bank’s influence on banks’ ability to lend loans and dependence of non-banks on loans as the source of financing. The factors were consequently applied to construe synthetic indices as measures of the total impact of these factors on the mechanism of monetary transmission through the bank credit channel. The analysis of the synthetic indices shows that between 1998 and 2002 there was a minor improvement of monetary transmission conditions.
DETERMINANTS OF BANK CREDIT CHANNEL IN THE LIGHT OF MULTIDIMENSIONAL COMPARATIVE ANALYSIS